Investigation of Pipe Inspection Robot by using Commercial Package - et. al., Nitin Sawarkar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There will be a great commercial and industrial advantage to the robot device competent of operating in lively pipelines. While a pipe is carrying fluid and pipe inspection is vital in order to recognize flaw owing to wear and corrosion. As Pipelines are usually obscured subversive, therefore they are getting in occurrence with soil and susceptible to deterioration. The wall thickness decreases efficiently due to oxidizing in wall of the steel pipe. The pipes and drains of many plants have recently become old and many robots have been built in the past to inspect these pipes. In several fields of manufacturing, inspection robots are used. The major application of the pipe inspection method is scrutinize the indoor of the channels and pipes, detecting and resolve troubles from the interior of channels or pipes